COMPETITIVE ENVIRONMENT FOR THE DEVELOPMENT OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP IN NEW UZBEKISTAN (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
The development of small businesses and private entrepreneurship is a cornerstone of economic growth and social stability in New Uzbekistan. This paper analyzes the role of a competitive environment in fostering entrepreneurial initiatives and creating opportunities for sustainable development. Key factors such as government support, access to financial resources, regulatory reforms, and the promotion of innovation are explored as drivers of small business growth.